2016
DOI: 10.1007/s10815-016-0801-6
|View full text |Cite
|
Sign up to set email alerts
|

Should preimplantation genetic screening (PGS) be implemented to routine IVF practice?

Abstract: As compared to day 3 blastomere (spp) biopsy followed by fluorescence in situ hybridization (FISH), PGS 1.0 [1], the utilization of trophectoderm biopsy (days 5-6 embryos) combined with comprehensive chromosome screening (CCS) tests for embryonic aneuploidy, PGS 2.0, has been suggested to improve in vitro fertilization (IVF) outcome [2], though not without criticisms [3,4]. Here, we draw attention to several underlying factors that will influence decisions to employ PGS 2.0 in routine clinical practice. PGS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…In well-informed patients with lethal aneuploidy/mosaic embryos and no euploid options, transfer of aneuploid or mosaic embryos may be warranted. This view is based upon the present literature, suggesting that a diagnosis of an aneuploid/ mosaic Babnormal^embryo is not always correct, or if it is correct, mosaicism detected at the blastocyst stage may not manifest as such in a live born [29][30][31]. While testing methodology is able to identify definitely normal and grossly abnormal chromosome complements in most cases, there is a significant, not well-delineated, gray zone into which many chromosome-screening results fall, mostly attributable to the problem of mosaicism.…”
Section: Pgs Assumptionsmentioning
confidence: 99%
“…In well-informed patients with lethal aneuploidy/mosaic embryos and no euploid options, transfer of aneuploid or mosaic embryos may be warranted. This view is based upon the present literature, suggesting that a diagnosis of an aneuploid/ mosaic Babnormal^embryo is not always correct, or if it is correct, mosaicism detected at the blastocyst stage may not manifest as such in a live born [29][30][31]. While testing methodology is able to identify definitely normal and grossly abnormal chromosome complements in most cases, there is a significant, not well-delineated, gray zone into which many chromosome-screening results fall, mostly attributable to the problem of mosaicism.…”
Section: Pgs Assumptionsmentioning
confidence: 99%
“…In the group of women older than 40 years studies with PGS on trophoblast cells have shown that a large number of embryos produced are chromosomally abnormal, thus explaining at least in part why there is such high BEmbryo Wastage^in this age group [16,34]. However, it remains to be seen whether this technique will ultimately lead to a significant improvement in live birth rate since it is still error-prone with the risk of discarding embryos wrongly diagnosed as aneuploidy because of mosaicism [21][22][23]. Other barriers such as the cost, including the possible need to cryopreserve embryos and defer transfer, and invasiveness of the biopsy and any potential long term effects also need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent improvements in pre-implantation genetic screening (PGS) techniques for identifying normal euploid embryos have been associated with higher pregnancy and delivery rates when analyzed per transfer [15][16][17]; however, several barriers to its widespread use still exist, including cost and particularly the lack of unequivocal evidence that its use improves pregnancy and live birth rates, particularly for patients with few embryos available for testing, due to the presence of high rates of mosaicism in the trophoblast cells [18][19][20][21][22][23]. Other studies have reported on the use of proteomics and metabolomics to identify factors in embryo culture media that may be predictive of embryo competence or assessing gene expression in cumulus cells; however, even these methods are still inefficient and not ready yet for clinical application [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…All are invasive, not completely reliable, costly, and likely result in the non-transfer/discard of some viable embryos. If one proposes pre-implantation genetic screening (PGS) for all blastocysts, there is now sufficient data to demonstrate that PGS is neither sensitive nor specific enough to select all euploid embryos, and there is accumulating data to demonstrate that this could ironically even lower live birth rates [10][11][12][13][14][15][16]. Indeed offering sophisticated embryo PGS testing (via array CGH or SNP or qPCR or next-generation sequencing (NGS)) has been shown to be impacted by high rates of trophectoderm embryo mosaicism [11,13,14], making the diagnostic accuracy very challenging with the risk of discarding some normal embryos that were incorrectly diagnosed as abnormal.…”
mentioning
confidence: 99%
“…Indeed offering sophisticated embryo PGS testing (via array CGH or SNP or qPCR or next-generation sequencing (NGS)) has been shown to be impacted by high rates of trophectoderm embryo mosaicism [11,13,14], making the diagnostic accuracy very challenging with the risk of discarding some normal embryos that were incorrectly diagnosed as abnormal. Therefore, the overall pregnancy rate might be decreased rather than increased [10,14,16]. But, all these methods are only selection, and not improvement of oocytes or embryos.…”
mentioning
confidence: 99%